2023
DOI: 10.31083/j.ceog5001013
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Surgery and Deep Infiltrating Endometriosis Treatment: The State of Art

Abstract: Objective: Surgical treatment of endometriosis, when indicated, has demonstrated to be effective in reducing painful symptoms and improve quality of life of patients affected with endometriosis. The minimally invasive approach via laparoscopy is the preferred method when compared with laparotomy but in the last two decades another minimally invasive approach has become available, the robotically assisted laparoscopic surgery. Robotic technology is widely used in different surgical branches, such as general sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…It has been shown that operative time decreases in relation to the increase in surgeries performed [ 37 ], as well as the condition of the patients and the severity of endometriosis [ 24 , 26 , 31 ], as mentioned before. Further prospective studies comparing laparoscopy to the new robotic systems are needed to address the controversial results that have been reported [ 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that operative time decreases in relation to the increase in surgeries performed [ 37 ], as well as the condition of the patients and the severity of endometriosis [ 24 , 26 , 31 ], as mentioned before. Further prospective studies comparing laparoscopy to the new robotic systems are needed to address the controversial results that have been reported [ 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%